Polymer sorbent for mercury removal from aqueous solution - N. A. A., Azman; Abdul Aziz, Mohd Azoddein; Mohd Faizal, Ali (IOP Publishing, 2020)
The research study the feasibility of polysulfide sorbent (PSS) by using waste palm cooking oil and low-cost sulphur for mercury removal from aqueous solution. Mercury is known as one of the most hazardous toxic heavy metal that gives harmful to human being and environment. PSS is one of the materials that act as adsorbent to remove heavy metals. Waste palm cooking oil was used to produce PSS thus also can solved waste cooking oil management in Malaysia. The efficiency of PSS was investigated in this study based on the study of effect of initial Hg (II) concentration, contact time, pH and polymer sorbent dosage for removal of Hg (II) ion in aqueous solution. The characterization of surface morphology was examined by scanning electron microscopy (SEM). From this study, the highest mercury removal was 95.57 % at 120 rpm of agitation speed, 4 hour of contact time, initial Hg (II) ion concentration of 1 mg/L, 2 g of sorbent dosage and pH 6.